Pengaruh Pemberian Infusa Lidah Buaya (Aloe vera.L) sebagai Antiseptik terhadap bakteri Escherichia coli - Reni, Putri; Wahyu, Sri; Dahlia, Dahlia; Kusumawardhani, Sri Irmandha; Idrus, Hasta Handayani (Indonesian Journal of Health, 2023)
Antiseptics are substances that can inhibit the growth and development of microorganisms. One of the microorganisms that cause diarrhea is Escherichia coli. Efforts to prevent infection is the use of antiseptics. One of the most useful antiseptics is Aloe vera.L. Aloe vera.L contains anthraquinones, saponins, flavonoids and tannins which have the ability to inhibit bacterial growth and are antiseptic. Method used Literature Review with Narrative Review Design. Results The lowest concentration of aloe vera extract (Aloe vera.L) which can inhibit the growth of Escherichia coli bacteria is at a concentration of 20%, while the most effective concentration of aloe vera extract (Aloe vera.L) can inhibit the growth of Escherichia coli bacteria at a concentration of 100%. Aloe vera extract (Aloe vera.L) is effective in inhibiting the growth of Escherichia coli bacteria.